Combined EGFR- and notch inhibition display additive inhibitory effect on glioblastoma cell viability and glioblastoma-induced endothelial cell sprouting in vitro. Issue 1 (December 2016) - Staberg, Mikkel; Michaelsen, Signe; Olsen, Louise; Nedergaard, Mette; Villingshøj, Mette; Stockhausen, Marie-Thérése; Hamerlik, Petra; Poulsen, Hans
Abstract Background For Glioblastoma (GBM) patients, a number of anti-neoplastic strategies using specifically targeting drugs have been tested; however, the effects on survival have been limited. One explanation could be treatment resistance due to redundant signaling pathways, which substantiates the need for combination therapies. In GBM, both the epidermal growth factor receptor (EGFR) and the notch signaling pathways are often deregulated and linked to cellular growth, invasion and angiogenesis. Several studies have confirmed cross-talk and co-dependence of these pathways. Therefore, this study aimed at testing a combination treatment strategy using inhibitors targeting the notch and EGFR pathways. Methods For evaluation of cell viability a standard MTT assay was used. Western blotting (WB) and Q-RT-PCR were employed in order to assess the protein- and mRNA expression levels, respectively. In order to determine angiogenic processes, we used an endothelial spheroid sprouting assay. For assessment of secreted VEGF from GBM cells we performed a VEGF-quantikine ELISA. Results GBM cells were confirmed to express EGFR and Notch and to have the capacity to induce endothelial cell sprouting. Inhibition of EGFR and Notch signaling was achieved using either Iressa (gefitinib) or the gamma-secretase inhibitor DAPT. Our data showed that DAPT combined with Iressa treatment displayed increased inhibitory effect on cell viability and abrogated expression and activation of major pro-survival pathways. Similarly, the combinational treatment significantly increased abrogation of GBM-induced endothelial cell sprouting suggesting reduced GBM angiogenesis. Conclusion This study finds that simultaneous targeting of notch and EGFR signaling leads to enhanced inhibitory effects on GBM-induced angiogenesis and cell viability, thereby stressing the importance of further evaluation of this targeting approach in a clinical setting.